Uses of literacy: aspects of working class life with special reference to publications and entertainments - Hoggart, Richard (England, 1957)
Mass literacy has opened new worlds to new readers. How far has it also been exploited to debase standards and behaviour? Have the magazines, books and films "for the millions" proved, on balance, a social benefit or a social danger? The author answers these questions.
Keywords: Middle classes